Genetic diversity of Stryphnodendron adstringens (Mart.) Coville determined by AFLP molecular markers - de Mendonca, Patricia Calligioni [UNESP]; Bertoni, Bianca Waleria; Amui, Saulo Franca; Giuliatti, Silvana; Conde Correa, Valeria Sieiro; Franca, Suzelei de Castro; Soares Pereira, Ana Maria (Pergamon-Elsevier B.V. Ltd, 2012)
Bark extracts of Stryphnodendron adstringens (Mart) Coville a Leguminosae species, well known in Brazil as barbatimao, are popularly used as healing agent. The objective of this work was to determine the genetic diversity of S. adstringens populations and to correlate genetic distances to the production of tannins. S. adstringens accessions from populations found in Cerrado regions in the states of Goias, Minas Gerais and São Paulo were analyzed using the AFLP (Amplified Fragment Length Polymorphism) technique. A total of 236 polymorphic bands were scored and higher proportion of genetic diversity was found inter populations (70.9%), rather than intra populations (29.1%). F-ST value was found to be significantly greater than zero (0.2906), demonstrating the complex genetic structure of S. adstringens populations. Accessions collected in Cristalina, GO, showed higher percentage of polymorphic loci (87.3%) and the highest genetic diversity. The lowest genetic variability was detected among accessions from the population growing in Caldas Novas, GO. The genetic distance among populations was estimated using the Unweighted Pair Group Method with Arithmetic Mean (UPGMA), which grouped populations into 3 clusters. Moreover, chemotypes with tannin concentration above 40% showed higher genetic similarity. AFLP analysis proved to be an efficient gene mapping technique to determine the genetic diversity among remaining populations of S. adstringens. Obtained results may be employed to implement further strategies for the conservation of this medicinal plant. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Cerrado; Leguminosae; Barbatimao; Conservation; Tannin